POLICY IMPLICATION ANALYSIS PUBLIC SPHERESIN THE CITY OF BANDUNG IN 2022 (Multicase Study Intertwined with Cikapundung Terrace and Cihampelas Terrace) - Wawan Gunawan (Jurnal Caraka Prabu, 2024)
Since serving as Mayor of the City of Bandung for the 2014 - 2019 period, Ridwan Kamil has been intensively building public spaces. Two of them are the Cikapundung Terrace and the Cihampelas Terrace. Although both are public spaces that provide open access for anyone to interact, they have different characters. The Cikapundung terrace is mor e driven by efforts to educate people to love the environment and rivers, while the Cihampelas terrace is more an effort by the Bandung City government to organize street vendors so that it does not cause traffic jams along the Cihampelas road. This policy has a positive impact on the one hand, but on the other hand it has a negative impact on other parties. For example, the construction of the Cikapundung terraces and the Cihampelas terraces has had a negative impact on the economic conditions of the peopl e who used to earn good fortune along the Cihampelas sidewalks and around Kampung Kolase, which is now the Cikapundung terraces. Thus government policies have an impact on society. As Dye (1981) said that the impact of a policy is the overall implication o r impact caused by a policy. Therefore this study will focus on analyzing the impact of public sphere development policies with a focus on the Cikapundung terraces and Cihampelas terraces using qualitative methods using the Multicase Intertwined Study tech nique from Robert K. Yin (2013). It is hoped that through this research an overview of the implications of public sphere policies for the people of the city of Bandung can be obtained.